Implementation of the Approach Measurement of Inclusive Financial Index in the Five Best Sharia Banks in Indonesia - Fatmawati, Naning (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Islamic banks carry out their role as intermediaries with Islamic principles. Inclusive finance is an effort to realize that all people in the community can enjoy facilities in the financial system. The purpose and objective of inclusive finance is to eliminate all obstacles in any form to the access of the entire community to use services in financial services supported by existing facilities. The financial inclusion index is an index to measure how much services to inclusive finance have been utilized by a country. This study aims to analyze the Category of Accessibility Index, Avalability and Usability at BSM, Muamalah Bank, BNI Syariah Bank, BRI Syariah and Mega Syariah Bank. In addition, t also analyzes the BSM Financial Inclusive Index category, Bank Muamalah, Bank BNI Syariah, BRI Syariah and Bank Mega Syariah. This study uses descriptive non-statistical quantitative research methods The results of this study indicate that Bank Muamalat and Bank Syariah Mandiri have a high category of accessibility and usability index, however for the Avalability Index, Bank Muamalat is in the medium category and Bank Syariah Mandiri is in the high category. BRI Syariah and BNI Syariah have a medium category for the Index of Accessibility, Availability and Usability. Meanwhile, Bank Mega Syariah has a low category for the Index of Accessibility, Availability and Usability. The Financial Inclusion Index is in the high category at Bank Muamalat and Bank Syariah Mandiri, for BRI Syariah in the medium category and Bank Mega Syariah in the low category.